Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27238525
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils Encapsulated in Zeolite Structures as Delivery Systems (EODS): An Overview

Abstract: Essential oils (EO) obtained from plants have proven industrial applications in the manufacturing of perfumes and cosmetics, in the production and flavoring of foods and beverages, as therapeutic agents in aromatherapy, and as the active principles or excipients of medicines and pharmaceutics due to their olfactory, physical-chemical, and biological characteristics. On behalf of the new paradigm of a more natural and sustainable lifestyle, EO are rather appealing due to their physical, chemical, and physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 140 publications
0
9
0
Order By: Relevance
“…The adsorption capacity of MS2 was constant, reaching 11.5% at 30 min, and did not change with time. As it was mentioned above, some types of zeolites are characterized by antimicrobial properties per se , , especially faujasite mineral. , It may be assumed that the MS2 bacteriophage was characterized by lower resistance to CBV-600 than to BMV and CCMV. The adsorption capacity increased for CBV-600 modified with silver and zinc cations in comparison with pure CBV-600 (see Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption capacity of MS2 was constant, reaching 11.5% at 30 min, and did not change with time. As it was mentioned above, some types of zeolites are characterized by antimicrobial properties per se , , especially faujasite mineral. , It may be assumed that the MS2 bacteriophage was characterized by lower resistance to CBV-600 than to BMV and CCMV. The adsorption capacity increased for CBV-600 modified with silver and zinc cations in comparison with pure CBV-600 (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, clinoptilolite (natural zeolite) is used as a food additive providing essential minerals for individuals and may be used as an adsorbent of harmful substances that contaminate the environment, air, water, and food. Zeolites are characterized by antimicrobial properties per se and may also be combined with nanoparticles, increasing their antimicrobial effect. , It was shown that composite materials containing clinoptilolite manifest antibacterial activity toward E. coli and S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinoptilolite is regarded as the most important and plentiful natural zeolite. It is located in large deposits all around the world and is widely utilized on a global scale in different research together with essential oil delivery systems [1,2,3,4]. Zeolites, due to their heterogeneity, are substances that are easily isolated from the postreaction mixture, restored and reused in the process [4].…”
Section: Introductionmentioning
confidence: 99%
“…EOs are considered as safe by FDA (Food and Drug Administration) and are known as GRAS (General Recognize as Safe) [22]. To overcome their direct loss trough evaporation process new technologies have been proposed such as their adsorption on natural adsorbents such as nanoclays, natural zeolites and activated carbons followed by their incorporation in polymer matrix to develop an active packaging film with controlled release of EOs in food [23][24][25][26][27][28]. Natural zeolite (NZ) is more favorable for use as a nanocarrier host of EOs than nanoclays due to its higher surface area.…”
Section: Introductionmentioning
confidence: 99%